Removal Copper from Water Using Columns Experiment of Lignite, Shale, and Ironsand - , TY BOREBOREY ([Yogyakarta] : Universitas Gadjah Mada, 2012)
harmful to the health. Experimental studies on column test by utilizing lignite, shale, and ironsand were carried out to determine the characteristic in term of quality, adsorption capacity and to know the most effectiveness of absorbent materials (between lignite, shale, and ironsand) in copper removal. In this study, prior to the treatment, lignite, shale, and ironsand were characterized by means of XRD, SEM/EDX, and XRF. Solution of copper was mixed into highly harmful concentration is about 7ppm. In the course of treatment, lignite, shale, and ironsand were selected into different grain size of 10 mesh and 25 mesh in the same amount of 300g. The six PVC columns were designed into 30cm of its height and 6cm of its diameter. Then the treatment process was carrying on 24h by flow vertically of solution copper through columns in the stable velocity of 0.005ml/s. After the treatment, solution copper was analyzed for the concentration of copper remained